Banana bunchy top disease - Niyongere, C.; Omondi, Bonaventure Aman Oduor; Blomme, Guy (CAB International, 2015)
Among diseases caused by viruses, banana bunchy top disease (BBTD) caused by Banana bunchy top virus (BBTV) is considered to be the most serious disease affecting banana crops worldwide. This chapter describes the current distribution, transmission and aphid vector (Pentalonia nigronervosa) of BBTV, as well as the disease incubation period, incidence, symptoms, detection and control. It is concluded that BBTD remains a serious threat to banana production in most affected countries and continues to spread in the absence of any meaningful control measures. It is suggested that the development of integrated management strategies should consider various factors, including agroecological practices such as the use of tolerant varieties and climatic factors, as well as socioeconomic aspects based on collective/community approaches to the eradication of affected mats to reduce virus inoculum, together with the availability and accessible cost of indexed virus-free planting materials.